# Thread: The practice paper based test on the ets website

1. ## The practice paper based test on the ets website

Hello I am taking the Gre on July 22 and I wanted to know if there is anyone who has the explanations to the practice paper based test on the ets website. And I would also like the explanations for the practice problems on the Preparing for the Verbal and Quantitative Sections of the Gre General Test. I am having a hard time trying to figure some of the questions out. Also if I just study the test prep on the ets website how well will I do I am not very good at math. Thanks for your time.  Reply With Quote

2. Hi I only have a website for the New GRE, not the current one. But how about you post the questions here and we can help you out with them  Reply With Quote

3. If 3 times Janes age, in years, is equal to 8 times Beths age, in years, and
the difference between their ages is 15 years, how old are Jane and Beth?  Reply With Quote

4. Let J represent Jane and B represent Beth.

3 * J = 8 * B

Now for the second equation we need to know who the older person is. We can use the first equation to tell us who is older. Either do:
J = 8/3 * B (this tells us that J is almost 3 times the age of B)

OR

B = 3/8 * J (this tells us that B is less than 1/2 the age of J)

So now we know J is older than B. The second equation will be J - B = 15.
Now we need to solve the system of equations
3*J = 8*B
J - B = 15

I will solve the second equation for J and plug it into the first equation
J = 15 + B
3 * (15 + B) = 8 * B
45 + 3*B = 8*B
45 = 5*B
B = 9

Now we can plug B back into any equation. I will choose the equation J - B = 15
J - 9 = 15
J = 24

Therefore, Jane is 24 and Beth is 9. You can plug the values back in to the original two equations to check your work.  Reply With Quote

5. Originally Posted by leckie504 if 3 times janes age, in years, is equal to 8 times beths age, in years, and

the difference between their ages is 15 years, how old are jane and beth?
3j = 8b

j-b = 15, j = b +15

3(b+15)=8b
3b+45 = 8b
b= 45/5 = 9

j = 9+ 15 = 24  Reply With Quote

6. In the coordinate system below, find the
(a) coordinates of point
Q

(b) perimeter of
PQR

(c) area of
PQR

(d) slope,
y-intercept, and equation of the line passing through
points
P and R

19. In the
xy-plane, find the
(a) slope and
y-intercept of a graph with equation 2y  x  6
(b) equation of the straight line passing through the point (3, 2) with

y
-intercept 1
(c)
y-intercept of a straight line with slope 3 that passes through the
point (2, 1)
(d)
x-intercepts of the graphs in (a), (b), and (c)

33  Reply With Quote

7. I cant figure out how to paste the angle but I uploaded it as an a attachment.  Reply With Quote

8. 17. If 3 times Jane’s age, in years, is equal to 8 times Beth’s age, in years, and
the difference between their ages is 15 years, how old are Jane and Beth?
18. In the coordinate system below, find the
(a) coordinates of point
Q

(b) perimeter of
PQR

(c) area of
PQR

(d) slope,
y-intercept, and equation of the line passing through
points
P and R

19. In the
xy-plane, find the
(a) slope and
y-intercept of a graph with equation 2y +x =6
(b) equation of the straight line passing through the point (3, 2) with

y
-intercept 1
(c)
y-intercept of a straight line with slope 3 that passes through the
point (2, 1)
(d)
x-intercepts of the graphs in (a), (b), and (c)

33  Reply With Quote

19.
(a) We can put the equation in slope intercept form where it is easy to see the slope and y-intercept.
Slope intercept form: y = m*x + b, where m is the slope and b is the y-intercept
2y + x = 6
2y = 6 - x
y = 3 - x/2 = -x/2 + 3 = -1/2 * x + 3

Therefore, the slope is -1/2 and the y-intercept is 3.

(b) Here they gave us one point (3, 2) and told us the y-intercept is 1. There are two approaches we can use to solve the problem from here.

Approach 1:
y = m*x + b
Since the y-intercept is 1, b = 1
y = m*x + 1
Now we can plug in the point (3,2) for x and y.
2 = m * 3 + 1
1 = 3m
m = 1/3
So the equation of the line is:
y = 1/3 * x + 1

We can plug in the point (3,2) to verify that we did everything correctly

Approach 2:
Since the y-intercept is 1, we know that b = 1 and that the point (0, 1) is on the line.
Now we can find the slope between (3,2) and (0,1) as:
(2 - 1) / (3 - 0) = 1/3
Now we can give the equation of the line as:
y = 1/3 * x + 1

We can plug in the point (3,2) to verify that we did everything correctly

(c) y = 3 * x + b
Now plug in the point they give you.
1 = 3 * 2 + b
-5 = b
So y = 3 * x - 5 is the equation of the line.

(d) The x-intercept is the point where y = 0.
x-intercept of (a): 2x + 0 = 6
x = 3 is the x-intercept

x-intercept of (b): 0 = 1/3 * x + 1
-1 = 1/3 * x
x = -3 is the x-intercept

x-intercept of (x): 0 = 3 * x - 5
5 = 3 * x
x = 5/3 is the x-intercept  Reply With Quote

10. Originally Posted by twohundredping 19.
(a) We can put the equation in slope intercept form where it is easy to see the slope and y-intercept.
Slope intercept form: y = m*x + b, where m is the slope and b is the y-intercept
2y + x = 6
2y = 6 - x
y = 3 - x/2 = -x/2 + 3 = -1/2 * x + 3

Therefore, the slope is -1/2 and the y-intercept is 3.

(b) Here they gave us one point (3, 2) and told us the y-intercept is 1. There are two approaches we can use to solve the problem from here.

Approach 1:
y = m*x + b
Since the y-intercept is 1, b = 1
y = m*x + 1
Now we can plug in the point (3,2) for x and y.
2 = m * 3 + 1
1 = 3m
m = 1/3
So the equation of the line is:
y = 1/3 * x + 1

We can plug in the point (3,2) to verify that we did everything correctly

Approach 2:
Since the y-intercept is 1, we know that b = 1 and that the point (0, 1) is on the line.
Now we can find the slope between (3,2) and (0,1) as:
(2 - 1) / (3 - 0) = 1/3
Now we can give the equation of the line as:
y = 1/3 * x + 1

We can plug in the point (3,2) to verify that we did everything correctly

(c) y = 3 * x + b
Now plug in the point they give you.
1 = 3 * 2 + b
-5 = b
So y = 3 * x - 5 is the equation of the line.

(d) The x-intercept is the point where y = 0.
x-intercept of (a): 2x + 0 = 6
x = 3 is the x-intercept

x-intercept of (b): 0 = 1/3 * x + 1
-1 = 1/3 * x
x = -3 is the x-intercept

x-intercept of (x): 0 = 3 * x - 5
5 = 3 * x
x = 5/3 is the x-intercept

OMG! Thank u so much!  Reply With Quote